1992
DOI: 10.2737/rm-gtr-217
|View full text |Cite
|
Sign up to set email alerts
|

Management recommendations for the northern goshawk in the southwestern United States

Abstract: This file was created by scanning the printed publication.Errors identified by the software have been corrected; however, some errors may remain.Reynolds, Richard T.; Graham, Russell T.; Reiser, M. Hildegard; and others. 1992. Management recommendations for the northern goshawk in the southwestern United States. Gen. Tech. Rep. RM-217, Ft. Collins, CO: U.S. Department of Agriculture, Forest Service, Rocky Mountain Forest and Range Experiment Station. 90 p.Present forest conditions -loss of a herbaceous and shr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
196
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(206 citation statements)
references
References 118 publications
5
196
2
3
Order By: Relevance
“…They reported that juveniles and adults were unlikely to flush at distances ≄12 m and ≄24 m from hikers, respectively. Finally, although not a study of 1998, Grubb et al 1998, Hamann et al 1999, Jones 1979, Reynolds et al 1992. b Sources: Delaney et al 1999, Swarthout and Steidl 2001, USDA FS 1997, Wasser et al 1997.…”
Section: Assessment Processes For Focal Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that juveniles and adults were unlikely to flush at distances ≄12 m and ≄24 m from hikers, respectively. Finally, although not a study of 1998, Grubb et al 1998, Hamann et al 1999, Jones 1979, Reynolds et al 1992. b Sources: Delaney et al 1999, Swarthout and Steidl 2001, USDA FS 1997, Wasser et al 1997.…”
Section: Assessment Processes For Focal Speciesmentioning
confidence: 99%
“…Some types of human disturbances to goshawk nests have been a suspected cause of nest abandonment (Reynolds et al 1992). In addition, roads and trails may facilitate access for falconers to remove young from nests (Erdman et al 1998).…”
Section: Focal Speciesmentioning
confidence: 99%
“…Area of the nest stand was determined to reflect conditions at a larger spatial scale (cf. goshawk's nest area; REYNOLDS et al, 1992), and at the same time to generate enough variation between the nests; analyses on a larger scale would yield only a little difference between sites due to the heterogeneous character of the NF.…”
Section: Discussionmentioning
confidence: 99%
“…WD, particularly coarse woody debris (CWD), has been shown to be an important structural and functional element in many forested ecosystems (Lambert et al, 1980;Sollins, 1982;Harmon et al, 1986;Spies et al, 1988). It provides a key habitat component (especially large logs) for many forms of wildlife (Reynolds et al 1992). Studies by Harvey et al (1981) and Harvey et al (1987) showed that organic materials, especially humus and buried residue in the advanced stage of decay, are excellent sites for the formation of ectomycorrhizal root tips.…”
Section: Introductionmentioning
confidence: 99%